Geese: A Valuable Genetic Resource for Meat Production - Tamzil, M.H.; Indarsih, B.; Syamsuhaidi, S. (Jurnal Biologi Tropis, 2025)
This article is a review written to provide information to readers about geese as livestock. Geese are herbivorous waterfowl with high genetic diversity. There are three centers of goose domestication in the world, namely Europe, China and Egypt. Geese can be developed as a meat producers as a functional food source, as well as by-products in the form of feathers which have high economic value. In order to produce high performance, geese need a balanced feed, which contains enough metabolic energy, crude protein and macro minerals. Geese can be developed as an alternative poultry meat producer to meet the need for poultry meat from other chickens, ducks and muscovy ducks.